Oral candidiasis and the risk factors: a serial case reports - Tan, Erlyne; Suryana, Ketut (International Journal of Advances in Medicine, 2021)
Oral candidiasis (OC) is also referred as ‘thrush’ is caused by the infections of the tongue and other oral mucosal sites and characterized by fungal overgrowth and invasion of superficial tissues. The main causative agent of 95% OC cases is Candida albicans. The prevalence of fungal oral infection was increased due to the increasing use of antibiotic and immunodeficiency condition. However, many factors have been suggested as risk factors for oral colonization. These predisposing factors are divided into local and systemic factors. We present two cases of patient with oral candidiasis that have admitted at Wangaya Regional Hospital, Denpasar, Bali, Indonesia with different precipitating factors in order to remind health provider that oral candidiasis does not only occur in people living with HIV/AIDS (PLWHA).